POTENTIALS OF ISLAMIC SOCIAL SECURITY IN ADDRESSING SOCIAL CRISES IN NORTH WESTERN NIGERIA - Sani, Abubakar; Haruna, Aminu (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
Islam is a humanitarian religion that addresses all social imbalances among people for its betterment in this world and the hereafter. It naturally pointed out in the Qur'an and Sunnah that the state (government) and wealthy segment of the Muslim society must render care and benevolence to the poor class within and outside their localities. These social programs are meant to improve the social conditions of the people to live happily as relatives and provide protection to themselves and society in general. This system was used in the early period of Islam to reduce inequality gaps and provide mutual living among Muslims. The social crises confronting the people of the North-western part of Nigerian society could lead to the total collapse of the region due to banditry, kidnapping, cattle rustling and other devastating social problems affecting the area. This paper adopts qualitative methods from library literature and observation to analyse its findings. The research observes that the involvement of middle and young people in these social problems results from moral decadence and poverty, among other issues. Finally, this work recommends general character reorientation, general public welfare awareness, remodelling of Islamic charity structure, establishing sustainable entrepreneurship programs etc.